Kajian Kriminologis Penyalahgunaan Narkotika Jenis Sabu Berdasarkan Teori Anomie Di Kecamatan Pondok Aren, Tangerang Selatan - Supriyanto Supriyanto; Lucky Nurhadiyanto (Deviance Jurnal kriminologi, 2017)
This study discussed the abuse of methamphetamine-type narcotics based on the Anomie Theory in Pondok Aren District, South Tangerang City. The purpose of this study was to find out the purpose and ways of abusing crystal methamphetamine. The discussion of this problem is analyzed using the Anomie Theory from Robert K. Merton to see the purpose and ways of abusing methamphetamine-type narcotics. At this writing using a qualitative approach method by way of digging information directly with informants to obtain the necessary data. This is done to find out the main problems contained in the case raised. The descriptive method is a method of using the present tense to study the state of a human group, an object, a set of conditions, a system of thought, or a class of events. The results of the study show that the reasons for the perpetrators to use and distribute narcotics are for fun and for personal gain. Meanwhile, the prevention and prosecution of narcotics cases carried out by the South Tangerang Police narcotics unit is quite good, but cooperation between the community and law enforcement is needed to prevent further narcotics crimes.